El juego y las estrategias metodológicas en niños de preparatoria de la Unidad Educativa “Huertas” periodo académico 2023-2024 - Peñaloza Aguilar, Fátima Lissett (2024)
The research project the game and methodological strategies in high school children of the Educational Unit "Huertas" academic period 2023-2024. The main objective of this project is to analyze the game as a methodological strategy in high school children, and to complement it, specific objectives are proposed, which consist of identifying the benefits of the game, characterizing the development of cognitive, socio-affective, linguistic and motor skills, and determining the main methodological strategies applied by teachers. The research is based on the need to transform traditional educational practices to ensure meaningful and holistic learning, as pointed out by previous studies. It uses a descriptive methodology that allows the systematic exploration of the educational reality and the identification of difficulties in the implementation of the game. The inductive-deductive method is used to infer and analyze specific facts, starting from both the general and the particular. Likewise, the analytical and synthetic method is used to decompose and then integrate the information obtained during the analysis process. Therefore, the research approach is qualitative, which implies collecting data to understand the experiences, perceptions and meanings behind the use of the game as an educational strategy. It seeks to evaluate the quality of the information obtained and to analyze it in order to achieve a comprehensive interpretation. The study reveals that, in spite of recognizing the benefits of play in child development, the observed practice shows a limited and unsystematic integration of play in daily high school activities, thus underlining the urgent need to improve planning and consistency in the application of play as an educational strategy in the classroom. Key words: Children's Play, methodological strategy, innovative methodological strategies, cognitive development